The legality and feasibility of the use of compulsory licensing under the trips agreement to facilitate the transfer of environmentally sound technologies under the UNFCCC regime - Hahn, Lily Maya (Department of Public Law, 2025)
The primary objective of the United Nations Framework Convention on Climate Change is to attain stability in the concentrations of greenhouse gases in the atmosphere. Considerable potential lies in mitigation technologies to lower the emission of these gases. Additionally, there is a crucial requirement for adaptation technologies to avert the risks posed by ongoing human disruption of the climate system. However, the transfer of environmentally sound technologies between countries, part of the broader concept known as technology transfer, faces challenges related to intellectual property rights. Developing nations argue that intellectual property rights hinder technology transfer, while developed nations consider them crucial for innovation and facilitation thereof. As a consequence of the disagreement on this topic, intellectual property rights were left out of the wording of the Paris Agreement and the scope and obligations of technology transfer under the climate regime remain open to varying interpretations. Resolving this issue requires reaching a consensus among stakeholders and finding a balance between international environmental law and intellectual property rights. One potential solution that is explored in this dissertation is the use of compulsory licensing under the Trade Related Aspects of Intellectual Property Agreement. This dissertation examines the existing legal framework governing the transfer of environmentally sound technologies relevant in the climate change context, analyses the interplay between international environmental law and intellectual property law, explores the Trade Related Aspects of Intellectual Property Agreement and assesses the legal viability and practical feasibility of compulsory licensing for climate purposes. Through this research, a better understanding of technology transfer in the international climate change regime is sought, and an interdisciplinary perspective on trade law and environmental law is provided.